Impact of the World Bank's ease of doing business rankings on compositions of FDI inflows - KIM, Anna (KDI School, 2016)
Foreign direct investment (FDI) inflow plays a substantial role in the growth and development of every country. Accordingly, the question of what drives FDI inflows has been explored and answered in the literature, as has been the positive correlation between FDI inflows and regulation indicated by the World Bank’s Ease of Doing Business Rankings (DBR). Relatively little studies has been conducted, however, on the effects of these rankings on the two FDI compositions of mergers and acquisitions (M&A) and greenfield FDI. This paper shows that improved DBR attracts significantly more FDI inflows, though the result becomes insignificant, albeit negative (as the DBR is measured in rankings, e.g. 1st is the highest rank.), when the sample narrows down to developing economies. Moreover, these findings suggest that greenfield FDI is more negatively impacted by regulations than M&A, though the effect is not significant. The analysis offered here has potentially important implications for governments regarding actions that can improve their DBR and generate the benefits associated with increased greenfield FDI, specifically increased capital and rising employment rates.
Thesis(Master) --KDI School:Master of Public Policy,2016